Genomics and molecular genetics of plant-nematode interactions - Jones, John.; Gheysen, Godelieve; Fenoll, C. (Carmen).; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
Plant parasitic nematodes often establish unique, sophisticated relationships with then hosts, dramatically influencing plant productivity. This book reviews the most recent developments in the molecular biology of plant-nematode interactions that have been driven by the application of genomics tools the book will be of interest to postgraduate students and to researchers with an interest in plant nematology and/or plant pathology more generally. A series of introductory chapters provide a biological context for the detailed reviews of all areas of plant-nematode interactions that follow and ensure that the Bulk of the book is accessible to the non-specialist. Chapters provide not just the exciting state of the art in each field, but also the experts' views of how they expect that research in each field would develop in the near future. A final section aims to show how these fundamental studies have provided outputs of practical relevance in agriculture. Book jacket.
Part I Introductory Chapters. 1. Introduction to Plant-parasitic Nematodes; Modes of Parasitism -- 2. Current nematode threats to world agriculture -- 3. Phylogeny and evolution of nematodes -- 4. Cyst nematodes and syncytia -- 5. Root-knot nematodes and giant cells -- Part II - Resources for functional analysis of plant-nematode interactions -- 6. Genome analysis of plant parasitic nematodes -- 7. Transcriptomes of plant-parasitic nematodes -- 8. Arabidopsis as a tool for the study of plant-nematode interactions -- 9. Transcriptomic and proteomic analysis of the plant response to nematode infection -- 10. C. elegans as a resource for studies on plant parasitic nematodes -- 11. Parallels between plant and animal parasitic nematodes -- 12. Degradation of the plant cell wall by nematodes -- 13. Suppression of plant defences by nematodes -- 14. Other nematode effectors and evolutionary constraints -- 15. Disease resistance-genes and defense responses during incompatible interactions -- 16. The role of plant hormones in nematode feeding cell formation -- 17. Unravelling the plant cell cycle in nematode induced feeding sites -- 18. The plant cytoskeleton remodelling in nematode induced feeding sites -- 19. Cell wall modifications induced by nematodes -- 20. Water and nutrient transport in nematode feeding sites -- Part IV - Applied aspects of molecular plant nematology: exploiting genomics for practical outputs -- 21. Molecular tools for diagnostics -- 22. Breeding for nematode resistance: use of genomic information -- 23. Biological Control of Plant-Parasitic Nematodes: Towards Understanding Field Variation Through Molecular Mechanisms -- 24. Nematode resistant GM crops in industrialised and developing countries.
Electronic reproduction.
Keywords: Nematode-plant relationships -- Genetic aspects; Plant nematodes -- Research; Electronic books